Specific Salt Effects on Poly(ethylene oxide) Electrolyte Solutions - Ren, Chun-lai; Tian, Wen-de; Szleifer, Igal; Ma, Yu-qiang (Macromolecules, 2011)
Exploring the mechanism of specific salt effects in electrolyte solutions is an old and attractive subject. It has been gradually realized that the competition at the molecular level plays an important role. Aiming to include molecular details as many as possible, we combine molecular dynamics (MD) simulations with a molecular theory to study specific salt effects on poly(ethylene oxide) (PEO) solutions with the addition of monovalent salt. Radial distribution functions obtained from MD simulations provide microscopic structures of different components as well as interactions between various species. On the basis of these interactions, we construct the molecular theory with four assumptions: (1) an ion along with bound water in the first shell works as a single entity; (2) short-ranged interactions among various species are modeled as hydrogen-bonding interactions; (3) the ability of a hydrated ion to provide donors/acceptors for hydrogen bonding is governed by the charge density; (4) contact ion pairs are included, especially in the cases of small cations. The molecular theory is generalized with the explicit inclusion of ion−PEO, ion−water, ion−ion, water−water, and water−PEO hydrogen bonds. This means the molecular-scale structure and interaction are included within the frame of the theory. Theoretically calculated cloud points verify that the salting-out ability for alkali metal ions follows the series of K+ > Rb+ > Cs+ > Na+ > Li+, which is in agreement with the experimental observations. Here, the competition among ion−PEO, ion−water, and water−PEO interactions and the impact of steric repulsions induced by the introduction of ions are two essential factors determining the phase behavior of PEO solutions. The combined methods bridge the microscopic interactions and structures to the macroscopic behavior.